Analisis Kemampuan Manajerial dan Kualitas Sumber Daya Manusia dalam Meningkatkan Kinerja Koperasi - Ucik Sinta Nuriya; Ainnur Rohmah; Nurus Sobakh (Indo Publishing, 2026)
Cooperatives are one of the important pillars in the economy that plays a role in improving the welfare of members through the principles of kinship and cooperation. In its implementation, the performance of cooperatives is influenced by various factors, including managerial ability and the quality of human resources. Good managerial skills are needed to carry out the functions of planning, organizing, directing, and supervising effectively, while the quality of human resources which includes knowledge, skills, and work attitudes is an important factor in supporting the success of cooperative operations. However, there are still cooperatives that experience obstacles in organizational management due to low managerial ability of administrators and suboptimal quality of human resources.This research aims to analyze managerial abilities and the quality of human resources in improving cooperative performance. The research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The research informants consist of administrators and cooperative members. The data analysis technique uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results of the study show that managerial skills have an important role in improving cooperative performance, especially in the aspects of planning, organizing, directing, and supervision. In addition, the quality of human resources which includes knowledge, skills, and work attitudes also supports the effectiveness of cooperative operations and services to members. This study concludes that the synergy between managerial ability and the quality of human resources is the main factor in improving cooperative performance optimally and sustainably.